2021
DOI: 10.1002/jts5.73
|View full text |Cite
|
Sign up to set email alerts
|

Blaming immigrants to enhance control: Exploring the control‐bolstering functions of causal attribution, in‐group identification, and hierarchy enhancement

Abstract: Blaming immigrants seems to be in part motivated by the need for control. However, three alternative explanations have been proposed as to why blaming bolsters feelings of control. First, blaming may restore a sense of an orderly world in which negative events can be attributed to a clear cause (causal attribution). Second, blaming others may strengthen in‐group identities thereby facilitating group‐based control (in‐group identification). Finally, blaming low‐status groups may enhance individuals' perceptions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 55 publications
1
4
0
Order By: Relevance
“…Despite this, we did find interaction effects between the personal control conditions and national narcissism in its continuous form on conspiracy beliefs about immigrants. This result extends previous literature on individuals' motivations to restore personal control through national narcissism (Cichocka et al, 2018;Marchlewska et al, 2020), and derogating immigrants (Hirsch et al, 2021), by suggesting that grouplevel control might influence intergroup conspiracy beliefs.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Despite this, we did find interaction effects between the personal control conditions and national narcissism in its continuous form on conspiracy beliefs about immigrants. This result extends previous literature on individuals' motivations to restore personal control through national narcissism (Cichocka et al, 2018;Marchlewska et al, 2020), and derogating immigrants (Hirsch et al, 2021), by suggesting that grouplevel control might influence intergroup conspiracy beliefs.…”
Section: Discussionsupporting
confidence: 86%
“…In Study 3, our goal was to investigate whether defensive group beliefs would be more pronounced when national narcissism is salient to compensate for low personal control. Previous findings indicated that low personal control increases defensive identification (Goode et al, 2017), and differentially affects the links between national ingroup positivity and outgroup hostility (Cichocka et al, 2018;Marchlewska, Cichocka, Panayiotou, Castellanos, & Batayneh, 2018), in line with the group-based control model (Fritsche et al, 2011(Fritsche et al, , 2013Hirsch et al, 2021). Furthermore, low personal control has also been reported to increase belief in specific conspiracy theories (Stojanov & Halberstadt, 2020).…”
Section: Studymentioning
confidence: 85%
“…One version of this claim suggests that some Americans trusted Donald Trump to look out for their economic interests more than other candidates or the traditional party system in the United States (e.g., Frank, 2016). Other varieties of this argument focus on a relationship between economic threat and ingroup–outgroup dynamics such as scapegoating immigrants (Hirsch et al, 2021; Stephan et al, 2005) or a more general relationship between economic threat and authoritarian attitudes (Feldman & Stenner, 1997; Rickert, 1998). There has been disagreement about how to operationalize distinct threats to group (e.g., racial/ethnic) status versus economic anxiety (Morgan, 2018; Mutz, 2018a).…”
Section: Studymentioning
confidence: 99%
“…Billig, 1988). Seen this way, immigrants serve as the horizontal nemesis, against which right-wing populists can build their rhetoric and mobilize their followers (Akkerman et al, 2017; Hirsch et al, 2021; Rothmund et al, 2020). Intergroup differentiation between ordinary people and immigrants leads to exclusionist populist beliefs (Bos et al, 2020; Hameelers & Fawzi, 2020), which may lead to political violence following the divisive rhetoric of right-wing populist leaders.…”
Section: Populism and Anti-immigrationmentioning
confidence: 99%